2019
DOI: 10.1155/2019/2761241
|View full text |Cite
|
Sign up to set email alerts
|

pNNS-Conjugated Chitosan Mediated IGF-1 and miR-140 Overexpression in Articular Chondrocytes Improves Cartilage Repair

Abstract: The aim of the present study was to investigate the effects of phosphorylatable nucleus localization signal linked nucleic kinase substrate short peptide (NNSp)-conjugated chitosan (NNSp-CS) mediated miR-140 and IGF-1 in both rabbit chondrocytes and cartilage defects model. NNSp-CS was combined with pBudCE4.1-IGF-1, pBudCE4.1-miR-140, and negative control pBudCE4.1 to form pDNA/NNSp-CS complexes. Then these complexes were transfected into chondrocytes or injected intra-articularly into the knee joints. High le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…This implies the necessity for research on ADAMTS5 in human skin aging, and, in doing so, this study demonstrated that the increase of biglycan and decorin protein levels occurred in NHDFs according to the decrease of ADAMTS5 expression, which were mediated by IGF-1 treatment or by ADAMTS5 siRNA transfection. In chondrocytes, several studies have reported that the expression of ADAMTS5 reduced by IGF-1 treatment as an aggrecan-degrading enzyme, which is identical to our results [ 54 , 55 ]. Therefore, our results indicated that ADAMTS5 may participate in the degradation of biglycan and decorin in the skin, and reduced ADAMTS5 expression by IGF-1 may play roles in reducing degradation of biglycan and decorin.…”
Section: Discussionsupporting
confidence: 92%
“…This implies the necessity for research on ADAMTS5 in human skin aging, and, in doing so, this study demonstrated that the increase of biglycan and decorin protein levels occurred in NHDFs according to the decrease of ADAMTS5 expression, which were mediated by IGF-1 treatment or by ADAMTS5 siRNA transfection. In chondrocytes, several studies have reported that the expression of ADAMTS5 reduced by IGF-1 treatment as an aggrecan-degrading enzyme, which is identical to our results [ 54 , 55 ]. Therefore, our results indicated that ADAMTS5 may participate in the degradation of biglycan and decorin in the skin, and reduced ADAMTS5 expression by IGF-1 may play roles in reducing degradation of biglycan and decorin.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of a practical or safe method to deliver miR-140 is an obstacle for real progress towards its intended use as a clinically usable therapeutic. To protect miR-140 from degradation and maintain its integrity and activity within the OA joint and synovium, considerable efforts have been made to develop strategies to improve miRNA delivery efficiency, such as chitosan nanoparticles [81], viruses and liposomes. For miR-140 therapeutic applications, these carriers should protect the RNA from degradation and accurately deliver the RNA to the desired cells, while avoiding delivery to nontarget cells.…”
Section: Mir-140 Delivery By Exosomesmentioning
confidence: 99%
“…The factors involved in cartilage regeneration include the cell migration to the site of injury, proliferation, expression of chondrogenic markers, production of bioactive peptides responsible for chondrogenic regeneration and differentiation into chondrogenic cell lineages (Armakolas et al, 2016, pp. 3066-3072;Clark et al, 2014;Garza-Veloz et al, 2013;Ikeda et al, 2017;Pasold et al, 2015;Tiwary et al, 2014;Zhao et al, 2014Zhao et al, , 2019.…”
Section: Cartilage Formation and Regenerationmentioning
confidence: 99%